Nutritional status among the children living in predominantly tribal block of Jhadol in district Udaipur, Rajasthan, India: A cross sectional study (Epidemiology, Biostatistics, and Public Health, 2022)
Background: India has achieved remarkable economic progress in last couple of decades but the fruit of progress has failed to assure the better nutritional status to our children. The child nutritional situation remains grim for most of the states, especially in the tribal region. This paper is an attempt to measure the extent of under nutrition in terms of Height/Length-for-age (stunting), Weight-for-height/Length (wasting), and Weight-for-age (underweight) for children less than five year old in predominantly tribal block Jhadol of district Udaipur, Rajasthan, India. Methods: World Health Organization (WHO) child growth standard has been used as reference population to measure the percentage prevalence of stunting, wasting and underweight from its median. Total of 1286 children (623male and 663female) have been considered for this study. WHO Anthro software has been used for analysis and interpretation of results.Results: The results showing the severe undernourishment among the children in this part of Rajasthan. 63% children are moderate to severely stunted (short for age), 46% has been found out to acutely malnourished and the composite index weight-for-age showing that 69% children is moderate to severely underweight. Against the popular facts that girls are more malnourished, boys of Jhadol block reported to be more undernourished.Conclusion: The high prevalence of chronic malnourishment in this part of Rajasthan is a matter of grave concern. This paper calls for a region specific policy based on holistic approach of better healthcare, ensuring food security, access to drinking water, sanitation.